Visuality and Experimentalism : Two Commented Examples in Contemporary Portuguese Poetry - Wolkoff, Gisele (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
While looking into the ways in which two contemporary Portuguese poets have helped bring visibility to visuality and experimentalism, this paper addresses two main issues: the public and the private present in poetic representations. It also points out to the location of feminine voices from and through experimentalism both as an aesthetic movement and as a tool towards the search for voice and belonging. My aim is to question the current validity of experimental poetry as a political practice.